1965
DOI: 10.1136/gut.6.6.540
|View full text |Cite
|
Sign up to set email alerts
|

Study of gastric acid secretion in hookworm duodenitis

Abstract: EDITORIAL SYNOPSIS An increased basal secretion has been demonstrated in hookworm duodenitis and its significance is discussed in relation to duodenal mucosal damage with consequent release of gastrin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

1967
1967
1976
1976

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 8 publications
0
3
1
Order By: Relevance
“…The depression of basal acid output, being out of proportion to the depression of histamine, stimulated acid secretion. These observations are in contrast with those of Raju and Narielvala (1965) who reported radiological evidence of 'duodenitis' in all their cases of hookworm infestation without irondeficiency anaemia. They also found basal hypersecretion of acid in these cases and suggested that 'duodenitis' and basal hypersecretion produced by the hookworms might lead on to duodenal ulceration.…”
Section: Methodscontrasting
confidence: 99%
“…The depression of basal acid output, being out of proportion to the depression of histamine, stimulated acid secretion. These observations are in contrast with those of Raju and Narielvala (1965) who reported radiological evidence of 'duodenitis' in all their cases of hookworm infestation without irondeficiency anaemia. They also found basal hypersecretion of acid in these cases and suggested that 'duodenitis' and basal hypersecretion produced by the hookworms might lead on to duodenal ulceration.…”
Section: Methodscontrasting
confidence: 99%
“…Gopalan (1959) and Konstam (1959) have suggested that hook worm infestation may have a possible role in causing peptic ulcer. This suggestion has been revived by the recent work of Raju and Narielvala (1965). In this series there were only five (1 %) patients who showed evidence of hook worm infestation.…”
Section: Discussionmentioning
confidence: 76%
“…Correction of iron deficiency in the former group leads to an improvement of gastric acid secretion (17,23,26,35). On the other hand, hookworm infection has been shown to cause duodenitis leading to an increase in basal acid secretion (29) and in stimulated acid secretion in response to a fractional test meal (5). Hookworm duodenitis may have been the basis of relative gastric hypersecretion in response to histamine in other studies -in hookworm-induced iron-deficient patients as compared to patients with non-hookworm associated iron deficiency (8) and in hookworm patients with abdominal pain as compared to those with out pain (6).…”
Section: Discussionmentioning
confidence: 99%
“…Iron deficiency of non-hookworm origin is generally associated with greater hyposecretion than that due to hookworm infection (6,8,14,18,29). Correction of iron deficiency in the former group leads to an improvement of gastric acid secretion (17,23,26,35).…”
Section: Discussionmentioning
confidence: 99%